The dynamics and endocytosis of Flot1 protein in response to flg22 in Arabidopsis - Yu, Meng; Liu, Haijiao; Dong, Ziyi; Xiao, Jianwei; Su, Bodan; Fan, Lusheng; Komis, George; Šamaj, Jozef; Lin, Jinxing; Li, Ruili (Journal of plant physiology, 2017)
Membrane microdomains play vital roles in the process of bacterial infection. The membrane microdomain-associated protein Flot1 acts in an endocytic pathway and is required for seedling development, however, whether Flot1 is a part of host defense mechanisms remains unknown. During an analysis of callose deposition, we found that Flot1 amiRNAi mutants exhibited defects in response to flg22. Using variable-angle total internal reflection fluorescence microscopy (VA-TIRFM), structured illumination microscopy (SIM) and fluorescence cross spectroscopy (FCS), we determined that the dynamic behavior of GFP-Flot1 in Arabidopsis thaliana cotyledon epidermal cells changed significantly in plants treated with the elicitor flg22. Moreover, we found that Flot1 was constitutively recycled via an endocytic pathway and that flg22 could promote endocytosis. Importantly, targeting of Flot1 to the late endosome/vacuole for degradation increased in response to flg22 treatment; immunoblot analysis showed that when triggered by flg22, GFP-Flot1 was gradually degraded in a time-dependent manner. Taken together, these findings support the hypothesis that the changing of dynamics and oligomeric states can promote the endocytosis and degradation of Flot1 under flg22 treatment in plant cells.
Keywords: fluorescenční mikroskopie; Endocytosis; Gene Expression Regulation, Plant; Microscopy, Fluorescence; Plants, Genetically Modified; flagelin; Arabidopsis Proteins; Cotyledon; VA-TIRFM; endocytóza; Flagellin; proteiny huseníčku; kotyledon; Flot1; geneticky modifikované rostliny; regulace genové exprese u rostlin; SIM; Dynamics; Arabidopsis